O Simples Nacional e os impactos da substituição tributária do ICMS - Corrêa, Cristiano de Souza (2014)
The taxation favoritism given to small businesses is a constitutional directive, in which the objective is the reduction, simplification or elimination of fiscal obligation, in order to provide a competitive advantage to these small businesses by enabling their development. In this sense, the publication of law number 123/2006, which was the creator of the simplified tributary regimen referred to as "Simples Nacional", effectively contributed to this demand defining beneficial rules that sought the differentiated treatment. On the other hand, the tributary substitution of ICMS has become one of the most controversial subjects in the fiscal and tributary arena since its implementation. The purpose of this study is to display the pertinent characteristics of the tributary substitution and the practical side effects for those whom choose to adopt the simplified tributary regimen. A comparative mathematical analysis was the methodology used to clarify the focal point of the aforementioned subject matter and its impacts on taxpayers. It has been concluded that the replacement of ICMS tax onerous decisively taxpayer under the Simples Nacional bringing disadvantages compared to other tax regimes